PERSPEKTIF ISLAM TERHADAP KEDUDUKAN PEREMPUAN DALAM HIKAYAT PUTRI SALAMAH - Desinta Zahra Setiani; Wirajaya , Asep Yudha (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research aims to understand the position of women from an Islamic perspective in Hikayat Putri Salamah. This research uses qualitative descriptive methods through document or text study. Data is obtained by recording quotations in Hikayat Putri Salamah that are by the research objectives. The data includes several quotations related to the Islamic view of the position of women in the Hikayat Putri Salamah. The data source is obtained from the transliteration of the thesis entitled “The Image of Women in the Ideal Concept of Hikayat Putri Salamah” by Alfiani. Data analysis was conducted using van Dijk's discourse analysis model which focuses on the three dimensions of the text. The results of the analysis were then studied in depth to be used as a foundation for finding the position of women through an Islamic perspective in the Hikayat Putri Salamah.  The research found that the text structure in Hikayat Putri Salamah includes macro structure, super structure, and micro structure. Through the results of the analysis, it was found that women have an equal position with men. However, there is a shift in the role of position when women have a husband. Women who have husbands are required to be submissive and devoted to their husbands so that women's positions are slightly below men's.